2019
DOI: 10.1177/0018578718823736
|View full text |Cite
|
Sign up to set email alerts
|

Role of Anti-inflammatory Drugs in the Colorectal Cancer

Abstract: Objective: The objective of this review was to systematically review and synthesize evidence regarding benefits of using nonsteroidal anti-inflammatory drugs (NSAIDs) for the treatment of colorectal cancer (CRC). Data Sources: The data sources were MEDLINE, PubMed, NEJM, Google Scholar, and Google searches of references from relevant and eligible trials. Review Methods: We screened abstracts and full-text articles of identified references for eligibility and reviewed randomized controlled trials, cohort studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Inflammation also participates in the development of CRC 18,19 . Inflammation can promote tumorigenesis and development by stimulating tumor cell proliferation and the release of inflammatory mediators 20 . CRC patients have immune dysfunction with a Th1/Th2 immune cell imbalance, drifting mainly toward Th2 cells 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation also participates in the development of CRC 18,19 . Inflammation can promote tumorigenesis and development by stimulating tumor cell proliferation and the release of inflammatory mediators 20 . CRC patients have immune dysfunction with a Th1/Th2 immune cell imbalance, drifting mainly toward Th2 cells 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, colorectal adenocarcinoma research has helped understand how the COX-2/PGE2 axis affects carcinogenesis and tumor progression. Sada et al indicates that COX-2/PGE2 overexpression can be observed early in benign lesions like adenomas ( 62 ). Therefore, it seems like the sustained overexpression of the COX-2/PGE2 axis favors adenocarcinoma progression in the context of unresolved chronic inflammation ( 19 ).…”
Section: The Tumor Microenvironment (Tme) and Inflammationmentioning
confidence: 99%
“…Several epidemiological and clinical studies supported the potential benefits of NSAIDs in the prevention and treatment of several cancers, including colon, ,, ovarian, breast, , lung, and prostate . In this context, long-term use of aspirin reduces the risk of colorectal, , ovarian, , breast, and prostate cancer and hepatocellular carcinoma. , Further, almost 90 clinical trials involving aspirin are being or have been carried out, such as the randomized phase II trial that demonstrated aspirin’s pharmacological efficacy in preventing colorectal cancer in patients at increased risk of colorectal cancer . Thus, the U.S. Preventive Services Task Force (USPSTF) recommended that aspirin can be used to help reduce the risk of cancers including colorectal cancer, although the long-term use of aspirin in older individuals is still being discussed , and needs further confirmation.…”
Section: Cancer Prevention and Treatmentmentioning
confidence: 99%